SPEAKING DESCRIPTION OF A MELANCHOLOGICAL TEMPERATURE PERSON - Adilova Nafisa Bahodirovna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article gives you information about temperament, how they are formed, their history, what types they are studied, and the description of speech